Bentuk, Dampak, dan Tantangan Open Government: Studi pada Institusi Badan Pengembangan Sumber Daya Manusia Industri DKI Jakarta - Teges Khithobi, Arya; Rachmalatri , Melinda; Bima Saktiawan , Andre; Parameswara Adianto , Indah (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2024)
This research aims to find out the forms, impacts, and challenges in implementing Open Government at the Industrial Human Resources Development Agency (BPSDMI) in DKI Jakarta province, Indonesia. A case study approach with data collection through interviews, observations, and literature review was used to explore the forms, impacts, and challenges of implementing Open Government at BPSDMI. The results of this research are interpreted through NVivo as a tool to analyze the research data. Referring to the context of the current digital era that makes it easier for people to compare government performance around the world, it is important to massively implement Open Government at BPSDMI to ensure that it continues to gain legitimacy and public support. Given that Open Government can encourage transparency, accountability, and public participation in government, it can indirectly improve the quality of BPSDMI's performance in managing public information as a democratic government institution.